2017
DOI: 10.15255/kui.2017.010
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Detection of Reinforcement of Building Materials with Piezoelectric Sensors

Abstract: The extensive use of reinforced materials in the construction industry has raised increased concerns about their safety and durability, while corrosion detection of steel materials is becoming increasingly important. For the scientific management, timely repair and health monitoring of construction materials, as well as to ensure construction safety and prevent accidents, this paper investigates corrosion detection on construction materials based on piezoelectric sensors. At present, the commonly used corrosio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Peng et al [143,144] also analysed sensors based on lead zirconate titanate and modified Fe, Mn, Ca (PZT-4-type), and La, Nb (PZT-5-type). On the whole, their results are close to those obtained in [142].…”
Section: Piezoelectric Sensorssupporting
confidence: 88%
See 1 more Smart Citation
“…Peng et al [143,144] also analysed sensors based on lead zirconate titanate and modified Fe, Mn, Ca (PZT-4-type), and La, Nb (PZT-5-type). On the whole, their results are close to those obtained in [142].…”
Section: Piezoelectric Sensorssupporting
confidence: 88%
“…Peng et al [142] suggested a piezoelectric sensor based on ceramics (lead zirconate titanate) and composite materials used to isolate the sensor, screen noise, and enhance the sensor's signal. The authors assessed the corrosion condition and the degree of damage to steel reinforcement based on the signal's amplitude.…”
Section: Piezoelectric Sensorsmentioning
confidence: 99%
“…It should be noticed that articles from other countries that focus on safety issues in the Indian construction industry were also considered in this study. The scope of this review-based study focused only on human-centered safety management and excluded other safety issues such as material or structural safety of buildings (Peng, 2017) that do not directly focus on construction employees' health and safety. Finally, a total of 64 journal documents were extracted after careful refining.…”
Section: Methodsmentioning
confidence: 99%
“…were also excluded. Further, it should be noticed that the the scope of this review-based study is human-centered safety management, it covered the safety planning and site management, but excluded other safety issues that do not direct focus on construction employees' safety, for example, structural or material safety for buildings (Peng, 2017). After the final round of screening, ultimately a total of 513 journal articles were selected as the literature sample for the follow-up scientometric analysis.…”
Section: Methodology 69mentioning
confidence: 99%